DROUGHT TOLERANCE OF WHEAT INTROGRESSIVE FORMS (Journal of Geography and Environmental Management, 2018)
In Kazakhstan the main limited factor for the wheat, growing up in arid lands is survival in thesummer, which make the studies on wheat drought resistance are very importance. It is interesting foradaptation to environmental drought to be combined physiological and biochemical indicators withtotal grain yield and productivity of wheat. The objects of the study were 12 introgressive forms of winterwheat, obtained from the crossbreeding of the varieties of winter wheat (Triticum aestivum L.) withwild relatives – Triticum timopheevii, Triticum militinae, Triticum kiharae, Aegilops cylindrical, Aegilopstriaristata, in the yield of 2015-2017.The drought tolerance of wheat genotypes in field experiments wasjudged by the absolute value of yield and the signs of productivity, as well as by the degree of declinein productivity under conditions of drought. Determination of drought tolerance in the laboratory wasconducted by the detection of free proline. Phenotyping, determine biomass accumulation and photosynthesiswas carried out on NDVI-technology. The experimental data were processed statistically andby cluster analysis.Screening of the results allowed to: reveal wide variability of the studied indicators; detect a changein the standardized index of vegetation differences, determined by the accumulation of vegetative biomassand phenological development phases of the studied wheat forms as well as obtained the bestgenotypes with the maximum of the NDVI indexes. The genotypes promising in breeding for droughtresistance that persistently retain a high level of free proline content have been identified. There werecomparative analysis of the introgressive forms and varieties by total yield, identification of promisingsimples by individual indicators and overall productivity. The results contribute to deciphering physiologicalmechanisms of growth and resistance of grain crops, intensification of wheat breeding for adaptabilityto environmental stresses, and enrichment of the genetic resources of Kazakh wheat with a varietyof prospective forms obtained from crossbreeding with wild relatives.